The book of Proverbs in social and theological context - Dell, Katharine J. (Katharine Julia), 1961- (Cambridge, UK ; New York : Cambridge University Press, 2006)
The book of Proverbs is the mainspring of the biblical wisdom tradition. Dell explores the possible social contexts for its varied material and provides an overview of the characterisation of its theology by scholars. She discusses how individual proverbs, instructions and poems came to form the collections we have today.
Social context(s) in Proverbs 1-9 -- Social context (s) in Proverbs 10:1-22:16 -- Social context(s) in Proverbs 22:17-31:31 -- Mention of Yahweh in Proverbs -- Theological context -- Echoes of other Old Testament texts and contexts in Proverbs.
Includes bibliographical references (pages 201-220) and index.
Print version record.
Master record variable field(s) change: 630
Keywords: Bible. -- Socio-rhetorical criticism; Bible. -- Theology; RELIGION -- Biblical Studies -- Old Testament; RELIGION -- Biblical Studies -- Wisdom Literature; Electronic books